UPAYA GURU DALAM PENGEMBANGAN KURIKULUM PENDIDIKAN AGAMA ISLAM DI SMA NEGERI 1 KERINCI - Aidil Akhyar; Mohamad Erihadiana (Pusat Penerbitan Universitas (P2U) Unisba, 2021)
Developing an Islamic Religious Education curriculum is a must carried out by Islamic Religious Education teachers. The development of this curriculum is an aspect that needs to be mastered by teachers, especially teachers of Islamic Religious Education. The research method used is qualitative methods. Teachers must have mature knowledge and readiness to develop the Islamic Religious Education curriculum. Teachers should not experience stagnation in teaching Islamic Religious Education. The dynamics of learning by developing the Islamic Religious Education curriculum will be realized if the teacher can develop the curriculum well.Keywords: Curriculum; Develop; Islamic Religious Education. AbstrakMengembangkan kurikulum Pendidikan Agama Islam merupakan keharusan yang diemban guru Pendidikan Agama Islam. Pengembangan kurikulum ini menjadi aspek yang perlu dikuasai oleh guru khususnya guru Pendidikan Agama Islam. Metode penelitian yang digunakan yaitu dengan metode kualitatif. Guru harus memiliki pengetahuan dan kesiapan yang matang untuk mengembangkan kurikulum Pendidikan Agama Islam. Guru jangan sampai mengalami stagnasi dalam membelajarkan Pendidikan Agama Islam. Kedinamisan pembelajaran dengan mengembangkan kurikulum Pendidikan Agama Islam akan terwujud jika guru bisa mengembangkan kurikulum dengan baik.Kata Kunci: Kurikulum; Mengembangkan; Pendidikan Agama Islam